Understanding the impact of the SARS-COV-2 pandemic on hospitalized patients with substance use disorder - King, Caroline (PLoS One, 2021)
BACKGROUND: The SARS-COV-2 pandemic rapidly shifted dynamics around hospitalization for many communities. This study aimed to evaluate how the pandemic altered the experience of healthcare, acute illness, and care transitions among hospitalized patients with substance use disorder (SUD). METHODS: We performed a qualitative study at an academic medical center in Portland, Oregon, in Spring 2020. We conducted semi-structured interviews, and conducted a thematic analysis, using an inductive approach, at a semantic level. RESULTS: We enrolled 27 participants, and identified four main themes: 1) shuttered community resources threatened patients’ basic survival adaptations; 2) changes in outpatient care increased reliance on hospitals as safety nets; 3) hospital policy changes made staying in the hospital harder than usual; and, 4) care transitions out of the hospital were highly uncertain. DISCUSSION: Hospitalized adults with SUD were further marginalized during the SARS-COV-2 pandemic. Systems must address the needs of marginalized patients in future disruptive events.